Landlocked Countries, Natural Resources and Growth: The Double Economic Curse Hypothesis - Banegas Rivero, Roger Alejandro; NuÃ±ez Ramirez, Marco Alberto; Salas Vargas, Jorge; Escobar Caba, Luis Fernando; Valdez del RÃo, SacnictÃ© (International Journal of Energy Economics and Policy, 2019)
In this paper, we discuss the hypothesis of a double effect of economic slowdown on economic growth, resulting by the income of natural resources and being a landlocked country. We considered the problem of heterogeneity as conditioned functions to quantile moments in response of economic growth. To do this, groups of 97 countries are considered for the period 1970-2014. The results suggest that the “double economic curse” presents an annual impact of -3% in quantiles of medium-low growth countries. Subsequently, additive effects between human capital and trade openness are evaluated to mitigate the lag impacts on growth: decreasing approximately between 20% and 40% of the negative effect for low growth countries and contracting around 10% and 50% for countries with medium growth rates. Keywords: Landlocked countries, economic growth, natural resources, human capital, trade openness, quantile regressions. JEL Classifications: O43, O47, O57, P48, C21 DOI: https://doi.org/10.32479/ijeep.8037